The Impact of AI on Management Education (International Journal of Scientific Research in Science and Technology, 2025)
Artificial Intelligence (AI) is revolutionizing management education by enhancing learning experiences, improving administrative efficiency, and providing data-driven decision-making capabilities. AI-powered tools, such as intelligent tutoring systems, machine learning algorithms, and virtual simulations, are reshaping traditional teaching methodologies. Recent studies indicate that AI-driven automation in education can improve learning outcomes by 30% while reducing administrative workload by 40%. AI enhances personalized learning, facilitates adaptive assessments, and supports real-time analytics for student performance tracking. However, challenges such as data privacy concerns, faculty resistance, and ethical implications remain barriers to full-scale AI adoption. This paper explores the impact of AI on management education, highlighting key benefits, challenges, and recent trends. It also discusses emerging technologies such as AI-powered virtual reality, peer-learning platforms, and blockchain-based credentialing. The study concludes that while AI holds immense potential to transform management education, institutions must address ethical concerns, provide faculty training, and ensure sustainable integration strategies. Future research should focus on developing inclusive AI frameworks that balance technology with traditional pedagogical methods to maximize learning outcomes and institutional efficiency.